MANAJEMEN PROGRAM BAHASA ASING DALAM PENCAPAIAN KEMAMPUAN BERBICARA BAHASA INGGRIS SANTRI - Hera Nurafni; Suwilah; Syamsuddin Ali Nasution; Zahra Khusnul Latifah (Fakultas Agama Islam dan Pendidikan Guru, 2022)
The foreign language program is one of the programs in an effort to improve students' foreign language skills. The importance of mastering English as an international language requires Islamic boarding schools to improve the quality of the program. This study aims to describe the management functions related to planning, organizing, implementing, and evaluating foreign language programs in achieving the ability to speak English in santri at Pondok Pesantren Modern Nurul Haramain NW Bogor. The research approach uses qualitative with the case study method (case study). This study uses data collection methods of observation, interviews, and documentation and analyzed with the stages of data reduction, data presentation, and drawing conclusions. The results of this study resulted in several findings including: 1) Planning of foreign language programs carried out at the general meeting early in the year, and the beginning of the formation of management; 2) Organizing foreign language programs consisting of Leaders, Field Coordinators, Language Advisory Councils and OPPM (Modern Islamic Boarding School Organizations); 3) The implementation of foreign language programs has been carried out well with the achievements of students although there are some obstacles; 4) Evaluation of foreign language programs is carried out on a weekly, quarterly, and semester basis. Evaluation of students is done by oral and written tests.